Evidence‐based therapy for atypical myopathy in horses. (1st March 2017) - Fabius, L. S.; Westermann, C. M.
Summary: The aim of this review is to establish the best therapy for equine atypical myopathy with a view to improving the survival rate. To this end, the currently used symptomatic therapy and literature on other metabolic diseases in horses or other animals have been analysed. The best treatment strategy consists of several elements. Advice with evidence: management with restricted movement, keeping warm, rehydration, glucose and insulin supplementation and administration of carnitine, vitamin E, selenium and riboflavin is advised. Acepromazine can be used as a muscle relaxant when indicated. Nonsteroidal anti‐inflammatory drugs should be used for pain relief. Regular emptying of the bladder might provide relief from some discomfort. Advice without evidence: laxatives or activated charcoal could be helpful. Contraindicated: Alpha 2 agonists as muscle relaxants because these drugs inhibit insulin release. Without further research glycine is also discouraged.